118 Awardee Talk - Genomic control of fatty acid profile in beef. (5th December 2019) - Shackelford, Steven D; King, Andy; Snelling, Warren; McDaneld, Tara G; Kuehn, Larry A; Bennett, Gary L; Wheeler, Tommy
Abstract: Steers (n = 868) were raised, feedlot-finished with ad libitum access to a high-energy diet and harvested to determine if there is genomic control of fatty acid profile traits in beef breeds common to the United States. Cattle included purebred and crossbred progeny of Angus, Red Angus, Hereford, Shorthorn, Simmental, Charolais, Limousin, Gelbvieh, Maine Anjou, Chiangus, Braunvieh, Salers, Brahman, Brangus, Santa Gertrudis, and Beefmaster as well as three composite lines. Either directly or through imputation, genotypes were determined for > 133, 000 functional single nucleotide polymorphisms (SNP). At approximately 38 h postmortem, a 2.54-cm-thick longissimus steak was obtained from the 13th rib region of the left side of each carcass. At 14 d postmortem, steaks were cooked and subsequently longissimus was pulverized in liquid nitrogen. Fatty acid profile was determined by gas chromatography and mass spectrometry. A genome-wide association study was conducted for fatty acid profile traits expressed as a deviation from the contemporary group mean using the Mixed Linear Model Analysis of SNP & Variation Suite 8.8.3 (Golden Helix) and Pre-computed Kinship Matrix using the GBLUP Genomic Relationship Matrix. A SNP in coiled coil domain containing 57 (CCDC57; Chromosome 19 at 51, 349, 695) affected the percentage of C14:0 (P < 10–46), short-chain fatty acids (P < 10–36), and saturated fatty acids (P < 10–17). Also, a SNP in thyroid hormone responsive (THRSP; Chromosome 29 at 18, 090, 403) affected the percentage of C14:0 (P < 10–16) and short-chain fatty acids (P < 10-10). The percentage of polyunsaturated fatty acids was affected by SNP in myostatin (Chromosome 2 at 6, 213, 980; P < 10–15). These results show that fatty acid profile of beef can be changed through genetic selection but, it is not clear if the level of change will be great enough to impact human health.